2017
DOI: 10.1515/eko-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

Variations of selected soil properties in the grass fields invaded and uninvaded by invasive goldenrod (Solidago canadensis L.)

Abstract: Although the invasion of exotic plants has been recognised as the serious cause of the biodiversity loss and natural habitats degradation and threat to the ecosystems functions, just the little attention has been paid to the potential impacts of the goldenrod invasion on the soil properties. Equally, currently obtained results are contrary and ambiguous. We tested whether the grass fields invaded and uninvaded by Canadian goldenrod (Solidago canadensis L.) differ in pH, soil moisture, organic carbon (Cox), hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Besides, the increase of the soil reaction simultaneously with the goldenrods density was observed too. However, the direct correlation is disputable because the impact of the Solidago invasion on the soil properties is very unambiguous [32].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the increase of the soil reaction simultaneously with the goldenrods density was observed too. However, the direct correlation is disputable because the impact of the Solidago invasion on the soil properties is very unambiguous [32].…”
Section: Discussionmentioning
confidence: 99%
“…There are many authors that describe how exotic plants and especially how Goldenrod affects physical properties. Some authors reported that invasion of S. gigantea significantly increase soil reaction [16,42], but the work of Quist et al [43] showed the opposite trend: that S. gigantea can lower the pH in a soil system they had invaded.…”
Section: Soil Physicochemical Propertiesmentioning
confidence: 99%
“…Therefore, an increasing number of studies have focused on its impact on the soil properties in invaded areas. [49,70,73,74] However, the results concerning the impact of Solidago invasion on the soil properties are contrary and ambiguous. The conclusions about the impact of invasion on the soil parameters are still not absolutely clear.…”
Section: Influence On the Physical And Chemical Properties Of Soilmentioning
confidence: 99%
“…The conclusions about the impact of invasion on the soil parameters are still not absolutely clear. [73] The results of some researchers suggest that S. canadensis can change the physicochemical properties of soils in invasive areas. Lu et al [75] studied the effects of different forms and levels of nitrogen (nitrate nitrogen and ammonium nitrogen) on S. canadensis and Artemisia lavandulifolia Candolle.…”
Section: Influence On the Physical And Chemical Properties Of Soilmentioning
confidence: 99%